2009
DOI: 10.4314/ijbcs.v3i4.47187
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of antibiotics susceptibility of isolates and plasmid analysis of Staphylococcus from surgical site infections in Nigeria

Abstract: There has been a significant increase in resistance of common bacterial isolates from surgical site infections in our community resulting in prolonged hospital stay, disability and deaths of patients. In this vein, we surveyed the antibiotic susceptibility profiles of aerobic bacterial isolates from postoperative wound infections and determined whether resistance in Staphylococcus aureus was genetically mediated. A total of 161 isolates were obtained from 153 swab samples of infected wounds using cultural, mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…We found Proteus spp (80%) to be most prevalent in burn wound infection as opposed to Staphylococcus aureus (42.9%) which was prevalent in acute soft tissue infection. Similar organisms were identified in acute soft tissue infections which include cutaneous abscesses, traumatic wounds, and necrotizing infection in which microbiological investigations showed that Staphylococcus aureus is the single causative bacterium in approximately 25 to 30% of cutaneous abscesses (22). This could be explained based on the fact that Staphylococcus aureus constitute the normal skin flora.…”
Section: Discussionmentioning
confidence: 77%
“…We found Proteus spp (80%) to be most prevalent in burn wound infection as opposed to Staphylococcus aureus (42.9%) which was prevalent in acute soft tissue infection. Similar organisms were identified in acute soft tissue infections which include cutaneous abscesses, traumatic wounds, and necrotizing infection in which microbiological investigations showed that Staphylococcus aureus is the single causative bacterium in approximately 25 to 30% of cutaneous abscesses (22). This could be explained based on the fact that Staphylococcus aureus constitute the normal skin flora.…”
Section: Discussionmentioning
confidence: 77%
“…A wound is a debilitated tissue that results from a breakdown in the skin giving rise to a physiological condition for microbial manifestation including opportunistic pathogens [ 43 , 44 ] affecting wound healing [ 45 ]. Depending on the degree of wound, whether acute or chronic, wound care is necessary to reduce infection or abnormal bacterial presence that may cause stress and other health consequences [ 44 , 46 ]. Over the years, wound dressing and healing have been problematic to clinicians [ 46 ].…”
Section: Wound Healing and Nanoparticlesmentioning
confidence: 99%
“…Depending on the degree of wound, whether acute or chronic, wound care is necessary to reduce infection or abnormal bacterial presence that may cause stress and other health consequences [ 44 , 46 ]. Over the years, wound dressing and healing have been problematic to clinicians [ 46 ]. Because there is no single appropriate wound dressing material that can act as a potent sterile antimicrobial agent capable of absorbing excess exudate, preserving the wound from external sources of infection, preventing excess heat at the wound, impermeable to gases, and a dressing that is easy to remove without further trauma to the wound [ 47 ] has complicated wound healing.…”
Section: Wound Healing and Nanoparticlesmentioning
confidence: 99%
“…S. aureus was also the predominant isolates in cesarean section, as it was reported by previous studies from Uganda and Nigeria, but the pattern in the distribution of the entire isolates was different. 47,48 In this study, the highest resistance which is exhibited by Enterobacteriaceae isolates was for ampicillin (91.3%), followed by augmentin (87%), cotrimoxazole (82.6%), and ceftriaxone (78.3). The resistance of Enterobacteriaceae isolates to ampicillin in this study was in line with previous studies conducted in Bahir Dar, Mekelle, Addis Ababa, and Hawassa, Ethiopia, as well as Uganda, which reported 88.2%-96.5%.…”
Section: Table 5 (Continued)mentioning
confidence: 60%